MONTENEGRO AND OLYMPISM - Dimitrije Rašović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
Montenegro is the current name appears 1276.year in the Charter of King Milutin. It was named after the high trees that are covering the hill Lovcen until the very tops of giving his country, viewed from the sea, "black" and the grim look. The beauty of Montenegro is full of contrasts which testify of its three regions: Coastal, Central and Mountain regions, which allows the conditions for engaging in all sports, especially sports belonging to the Olympic sports. Olympism itself has a long tradition in Montenegro, which dates before the Modern Olympic Games in Athens 1896.year and Montenegrins activity to find on the biggest sports festival back 1896.year.